The current state of intensive care unit discharge practices - Results of an international survey study - Hiller, Maike; Burisch, Christian; Wittmann, Maria; Bracht, Hendrik; Kaltwasser, Arnold; Bakker, Jan (Frontiers in Medicine, 2024)
Motivation: An increasing pressure on limited intensive care capacities often requires subjective assessment of a patient's individual discharge readiness in the absence of established ADT-guidelines (Admission, Discharge, Transfer). To avoid suboptimal care transitions, it is important to define objective guidance for the admission and discharge of intensive care patients and to optimize transfer processes between the intensive care unit (ICU) and lower care levels. For that, structured insights into usual ICU discharge and transfer practice are essential. Generating these was the aim of this study. It was focused on involved stakeholders, established processes, discharge criteria and tools, relevant performance metrics and barriers to timely and safe discharges.Method: In 2022, a structured, web-based, anonymous cross-sectional survey was conducted, aimed at practicing ICU physicians, nurses and bed coordinators. 29 questions (open, closed, multiple choice, scales) were divided into thematic blocks. The study was supported by several national and international societies for intensive care medicine and nursing.Results: 219 participants from 40 countries (105 from GER) participated in the survey. An overload of acute care resources with around 90% capacity utilization in the ICU and the general ward (GW) leads to premature but also delayed patient transfers due to a lack of available ward and intermediate care (IMC) beds. After multidisciplinary rounds with the intensive care team, the ICU clinician on duty usually makes the final transfer decision. One third coordinates discharge decisions across departmental boundaries. By the end of the COVID pandemic, half of the hospitals had ADT policies in place. Of these, a third had specific transfer criteria established, consisting primarily of vital signs and laboratory data, patient status and autonomy, as well as organization-specific criteria. Liaison nurses were less common but were ranked right after required IMC capacities for closing the care gap between the ICU and normal wards. 80% of the participants believed that transfer planning would be easier if there was good transparency of capacity utilization of lower care levels, a standardized transfer process and interdisciplinary communication.To improve care transitions, transfer processes should be managed proactively and across departments and care gaps should be closed.